2009
DOI: 10.1007/s10552-009-9386-z
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and risk of glioma: a meta-analysis

Abstract: Overall, results of pooling of all studies suggested that smoking is not associated with risk of glioma. However, the small but significant increased risk seen for cohort studies remains to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 56 publications
0
25
3
Order By: Relevance
“…No clear association has been found between smoking and incidence of other tumours of the CNS, including glioma or meningioma, either in this cohort (Benson et al, 2008) or in other studies (Mandelzweig et al, 2009). Possible mechanisms for an association between smoking and risk of acoustic neuroma include, as well as direct effects of tobacco carcinogens, the effects of cigarette smoking on hormonal status (Kapoor and Jones, 2005); female sex hormones may have a function in development of some central nervous system tumours, including acoustic neuroma (Benson et al, 2010).…”
Section: Discussioncontrasting
confidence: 70%
“…No clear association has been found between smoking and incidence of other tumours of the CNS, including glioma or meningioma, either in this cohort (Benson et al, 2008) or in other studies (Mandelzweig et al, 2009). Possible mechanisms for an association between smoking and risk of acoustic neuroma include, as well as direct effects of tobacco carcinogens, the effects of cigarette smoking on hormonal status (Kapoor and Jones, 2005); female sex hormones may have a function in development of some central nervous system tumours, including acoustic neuroma (Benson et al, 2010).…”
Section: Discussioncontrasting
confidence: 70%
“…However, previous epidemiologic research has not provided a clear indication of whether smoking can increase the risk of brain tumours. While most studies have failed to demonstrate any excess risks [5,13-20,25-27,30-32], some studies have found excess risks in their entire population or in some subpopulation [28,29,34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Among cohort studies, some found no association [25-27] and some found significant positive associations in women but not men [28] and in a study of women only [29]. A recent meta-analysis on smoking and glioma found no overall association when case–control and cohort studies were pooled, although there was a small but significant increased risk among cohort studies [30]. For meningioma, some case–control studies found no evidence of increased risk [16,27,31,32] and others found an association in one sex but not the other [17,18,33-35].…”
Section: Introductionmentioning
confidence: 99%
“…A study on a population of 22.946 icelanders, also found smoking as a risk factor of cancer for all sites, except endometrium (85). Multiple studies did not find any relation between smoking and glioma risk (82,(86)(87)(88), while others have mixed conclusions (89). Alcohol and cigarette smoking are not currently considered to be risk factors for malignant brain tumors (90).…”
Section: Lifestyle Factorsmentioning
confidence: 99%